Lipid composition of the brains of she-goat and castrated goat consumed in Ekiti State, Nigeria (Bangladesh Journal of Scientific and Industrial Research, 2015)
The levels of fatty acids, phospholipids and sterols were determined in the brains of she-goat and castrated goat found in Ekiti State, Nigeria by gas chromatography. Results showed that the crude fat levels were 9.98 and 10.2 % in the brains of she-goat and castrated goat respectively. The fatty acid composition of she-goat and castrated goat brain shows that the SFA was 40.6 and 42.7 %, MUFA was 37.1 and 38.7 % and PUFA was 20.9 and 22.3% respectively. The other parameters of she-goat and castrated goat brain were found: PUFA/SFA, 0.490 and 0.548; MUFA/SFA, 0.869 and 0.953; n-6/n-3, 0.775 and 11.7; LA/ALA, 0.876 and 28.0; AA/DGLA, 6.05 and 17.4; EPA/DHA, 1.00 and 5.89 and EPSI (PUFA/MUFA), 0.564 and 0.575 respectively. Phospholipids were present in she-goat and castrated goat with a value range of 2365 and 3047 mg/100g respectively. Among the sterols, only cholesterol was of any significant level with values of 1353 mg/100g (she-goat brain) and 1355 mg/100g (castrated goat brain). Linear correlation at ? = 0.05, df: n-1 showed that no significant difference exists between the crude fats, phospholipids and sterols except in the fatty acids parameters.Bangladesh J. Sci. Ind. Res. 50(2), 153-162, 2015